the indication of the scene as a symbolic system in the Iraqi theatrical (Al-Academy, 2022)
The theatrical view reflects various connotations and intellectual and aesthetic implications, as the view includes a symbolic geometric, architectural and archetypal connotation suggestive of reality and nature, as theatrical art is the woman that reflects reality, specifically the significance of the theatrical view that reveals to us the philosophical, aesthetic and cognitive dimensions of theatrical trends, so the research came with the methodological framework, which It included the research problem (what is the significance of the scene as a symbolic system in the Iraqi theatrical performance), the importance of the research and the need for it, the research objective, the limits of the research and the most important terms.As for the theoretical framework, the first topic was (the concept of symbolic significance), and the second topic (the symbolic significance of the scene in the theater).The research procedures included a description of the original research community, sample, method and tool, and the researchers chose a play (Reveals) as a sample for the current research. The research concluded with the most important results and conclusions that the research reached:1. The semantic expression of the scene is achieved as a result of color and shape working within a symbolic semantic system in terms of (make-up and fashion) that reflects the meanings and ideas of theatrical performance.2. The use of intentionality in the design in order to convey the aesthetic value of the components of the theater scene for the recipient, and the enjoyment of the theatrical performance.And then references, sources and a summary in English